2014
DOI: 10.1002/lary.24717
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of speech outcomes after total laryngectomy in the 21st century: A single‐center study

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
(49 reference statements)
5
46
1
Order By: Relevance
“…Results here are in concordance with other studies that found no significant difference in complication rates of primary and secondary TEP . Direct complications in the current study (64.6% and 60.9% for primary and secondary TEPs, respectively) were slightly higher than others reported, which may be explained by the comprehensive inclusion and prospective tracking of complications, long‐term follow‐up of 4.7 years, and high rate of radiotherapy (only 8.3% of this cohort did not require radiotherapy) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results here are in concordance with other studies that found no significant difference in complication rates of primary and secondary TEP . Direct complications in the current study (64.6% and 60.9% for primary and secondary TEPs, respectively) were slightly higher than others reported, which may be explained by the comprehensive inclusion and prospective tracking of complications, long‐term follow‐up of 4.7 years, and high rate of radiotherapy (only 8.3% of this cohort did not require radiotherapy) .…”
Section: Discussionsupporting
confidence: 92%
“…Direct complications in the current study (64.6% and 60.9% for primary and secondary TEPs, respectively) were slightly higher than others reported, which may be explained by the comprehensive inclusion and prospective tracking of complications, long‐term follow‐up of 4.7 years, and high rate of radiotherapy (only 8.3% of this cohort did not require radiotherapy) . TEP outcomes, as measured by long‐term use of TEP (82% for primary and 85% for secondary TEPs) were slightly higher than other reported rates of 75% to 78% for primary TEP and 67% to 71% for secondary TEP that have been published since the recent trend of increased frequency of salvage laryngectomy . As reported in several other studies, there was no significant difference in success rate (as measured by TEP use or fluency) between patients who received radiation and those who did not .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In our study, the majority of all groups underwent primary TEP and the rate of fistula was no higher in the reconstruction group (24%) than in those who underwent primary total laryngectomy (25%). Like Moon et al, we also found no difference in long‐term TEP success rates between those who had undergone primary versus salvage total laryngectomy.…”
Section: Discussionsupporting
confidence: 82%
“…This flap is a vascularized portion of fasciocutaneous tissue harvested from the volar surface of the forearm . Although there are some data about the impact of a circumferential RFFTT flap on voice outcomes after total laryngopharyngectomy, the impact of a partial pharyngectomy and a noncircumferential “patch” reconstruction with RFFTT has received relatively little attention in the literature and there is a need for long‐term outcome studies using validated functional as well as quality of life (QOL) measures . When reconstruction is performed, the reconstructed portion of the pharynx will contain an inert, adynamic flap of tissue, which may have an impact on the performance of the pharynx for both voice and swallowing.…”
Section: Introductionmentioning
confidence: 99%